THE INFLUENCE OF THE PROJECT ON STRENGTHENING PANCASILA STUDENT PROFILES, THE ROLE OF SCHOOL CULTURE, AND PARENTAL PARENTING ON THE CHARACTER OF SOCIAL CARE - Nuraini, Dewi Ratih; Rindrayani, Sulastri Rini; Rizqy Ana, Ria Fajrin (JURNAL SOCIUS, 2025)
Social care is a crucial dimension in the development of the Pancasila Student Profile (P5) and is a focus for strengthening character education at the junior high school level. This study aims to analyze the influence of the P5 Project, school culture, and parental care practices on the social care character of ninth-grade students at SMPN 8 Blitar. The quantitative approach used was a survey method, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The study sample consisted of 156 students selected using proportional stratified random sampling from a total population of 256 students. The results showed that the P5 Project and parental care practices had a positive and significant effect on students' social care character (p < 0.05). Conversely, school culture did not show a significant effect (p > 0.05). The structural model was found to be in good agreement with the SRMR value of 0.070 and NFI of 0.835. These findings emphasize the importance of synergy between the P5 program, the role of families through democratic parenting, and school culture in developing a socially responsible character.The study concludes that strengthening students' socially responsible character requires a collaborative approach between schools, families, and national policies based on Pancasila values. This study recommends increased parental involvement and school consistency in internalizing social values through project-based learning.